2014
DOI: 10.1002/jsc.1993
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Impact of Microcredit in Mali: An Evaluation by Propensity Score Matching

Abstract: During the last 30 years, the microfi nance industry has developed and spread around the world. Along with its development, there has been an increased focus on analyzing its impact on the wellbeing of the benefi ciaries. In Mali, microfi nance started in the 1980s, and recent successive governments were particularly interested in it as a tool for fi ghting against poverty and gender inequality. Th erefore, the implementation of microfi nance programs in this country took into account the situations of gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
3
8
0
2
Order By: Relevance
“…In particular, the empirical results of this study reveal that the household income, expenditures and savings increased by 1.15 percent, 1.13 percent, and 1.25 percent respectively per year. The findings of this study are similar to the studies that found a positive impact of microfinance on household income and expenditures (Hossain, 2012b;Rahman and Khan, 2013;Koloma and Alia, 2014;Attanasio et al, 2015;and Banerjee et al, 2015). It is worth noting that microfinancing is being provided to the poor who are unable to provide collateral and/or do not have access to commercial banks.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, the empirical results of this study reveal that the household income, expenditures and savings increased by 1.15 percent, 1.13 percent, and 1.25 percent respectively per year. The findings of this study are similar to the studies that found a positive impact of microfinance on household income and expenditures (Hossain, 2012b;Rahman and Khan, 2013;Koloma and Alia, 2014;Attanasio et al, 2015;and Banerjee et al, 2015). It is worth noting that microfinancing is being provided to the poor who are unable to provide collateral and/or do not have access to commercial banks.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have concluded that access to microfinance positively influences the poor, while others have expressed scepticism about the contribution of microfinance to the socio-economic development of the poor. For example, several recent studies claimed that microfinance has a significant positive impact on poverty reduction (see Biosca, Lenton, and Mosely, 2014;Koloma and Alia, 2014;Attanasio et al, 2015;Banerjee et al, 2015). On the other hand, some studies found no impact of microfinance on household income and expenditures (see Duvendack and Palmer-Jones, 2012;Augsberg et al, 2015, Angelucci, Karlan andZinman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research indicates that household size does not impact access to credit (Amendola et al 2017;Khoi et al 2013). However, other research indicates that there may be some relationship with household size but not to the number of children in the household (Koloma and Alia 2014).…”
Section: Hypothesis 4 (H4)mentioning
confidence: 94%
“…Income probably influences the behavioral variables and gaps in the behavior of the two groups positively. Gender plays an important role in realizing the benefits of microfinance (Koloma & Alia, 2014). A gender dummy variable is used, which takes a value equal to one of the individual is male, it takes the value zero if female.…”
Section: Empirical Analysismentioning
confidence: 99%